Subsurface Characterization using Electrical Resistivity Tomography (ERT) for Sponge City Planning in Nusantara Capital City (IKN), Indonesia: Karakterisasi Bawah Permukaan Menggunakan Geolistrik Resistivitas (ERT) untuk Perencanaan Kota Spons di Ibu Kota Nusantara (IKN), Indonesi - Wahidah, Wahidah; Lepong, Piter; Supriyanto, Supriyanto; Djayus, Djayus; Firdaus, Muhamad Akmal; Azisyarlina, Dwi (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
Clay shale dominates the lithology along access roads in the IKN development area. Its impermeable nature poses challenges to implementing the Sponge City concept, which relies on enhanced rainwater absorption to reduce surface runoff. This study aims to map the spatial distribution of clay shale and assess its implications for Sponge City planning. The geoelectrical resistivity method was applied at three sites, each consisting of one long section and three cross sections. Resistivity contrasts were used to delineate subsurface lithology, producing two- and three-dimensional models. The results reveal three main lithological units: topsoil, clay shale, and sandy clay. Topsoil shows heterogeneous resistivity values with thicknesses ranging from <1 m to 5 m. Clay shale exhibits resistivity values below 50 Ωm and thicknesses of <5–30 m, while sandy clay exceeds 50 Ωm with variable thicknesses up to 30 m. The thick, low-resistivity clay shale indicates poor permeability, which limits infiltration and groundwater storage. These findings suggest that the IKN area is less suitable for a natural sponge system. Therefore, stormwater management should prioritize engineered solutions such as green roofs, retention ponds, and bioretention facilities to control runoff and support sustainable urban development.